2014
DOI: 10.1089/ars.2013.5582
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Redox and Metabolic Oscillations in Mammalian Systems

Abstract: Significance: A substantial proportion of mammalian physiology is organized around the day/night cycle, being regulated by the co-ordinated action of numerous cell-autonomous circadian oscillators throughout the body. Disruption of internal timekeeping, by genetic or environmental perturbation, leads to metabolic dysregulation, whereas changes in metabolism affect timekeeping. Recent Advances: While gene expression cycles are essential for the temporal coordination of normal physiology, it has become clear tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 148 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…In humans and other mammals, circadian biological oscillations -with a period of about 24 h -influence a variety of behavioral and physiological processes pertaining to sleep, metabolism, immune function, etc. (74)(75)(76)(77)(78). Recently, it has been found that redox-dependent processes participate in the circadian rhythms along with genetic timekeeping clock processes (75,76,78,79), which supports possible participation of the Nrf2 pathway as it pertains to response to cellular redox status (74,77,(80)(81)(82).…”
Section: Nrf2 and Circadian Rhythmsmentioning
confidence: 81%
“…In humans and other mammals, circadian biological oscillations -with a period of about 24 h -influence a variety of behavioral and physiological processes pertaining to sleep, metabolism, immune function, etc. (74)(75)(76)(77)(78). Recently, it has been found that redox-dependent processes participate in the circadian rhythms along with genetic timekeeping clock processes (75,76,78,79), which supports possible participation of the Nrf2 pathway as it pertains to response to cellular redox status (74,77,(80)(81)(82).…”
Section: Nrf2 and Circadian Rhythmsmentioning
confidence: 81%
“…First, circadian cycles of Prx hyperoxidation seen in a variety of organisms were suggested to be a fundamental, transcription-independent mechanism underlying circadian clocks [97, 98]. However, there is no evidence yet that this is related to signaling, and rather than being a driver of rhythms, it may be a consequence of other rhythmic cellular activities.…”
Section: Potential Roles For Prxs In Stress and Non-stress Related Cementioning
confidence: 99%
“…1). Although ROS have mostly been regarded as harmful, recent work has emphasized the essential contribution of oxidant signaling in keeping intracellular molecular communications fast and efficient [27,28]. Accordingly, ATP low , NADPH high , ROS low T-cells lose the ability to swiftly mobilize ROS-sensing mediators.…”
Section: Ra T-cells – Energy-deprived T-cells With Impaired Redox Sigmentioning
confidence: 99%